MAKNA AKULTURASI HINDU BUDDHA PADA ARSITEKTUR CANDI PLAOSAN - Sahruni, Sahruni Sahruni; Birsyada, Muhammad Iqbal (Universitas PGRI Yogyakarta, 2021)
The purpose of this study was to see: (1) Hindu-Buddhist influence on the Plaosan Temple architecture, (2) The meaning of architecture and its relation to the Hindu-Buddhist tradition of the Plaosan Temple.The method used in this research is literature combined with observation and in-depth interviews to complement the data. Literature is sourced from books, journals and final reports of the after-retirement of the Central Java Cultural Heritage Conservation Center. Interviews involve historians, academics, and historical activists. The data collected is then processed and displayed so that it can be concluded.The results showed that (1) the combination of Hindu and Buddhist architecture can be seen from the ancillary temples and the ancillary stupas found in the Plaosan Temple complex. The Perwara Temple in the Plaosan Temple complex has Hindu architectural features which can be seen from the top of the temple which is shaped like a pearl, while the Perwara Stupa in the Plaosan Temple complex has Buddhist architectural features that can be seen from the top of the temple which is shaped like a stupa. (2) The Hindu-Buddhist acculturation at the Plaosan Temple complex reflects the harmony between the two religions. In addition, the Plaosan Temple complex is associated with 72 Perwara Temples and 268 Perwara Stupas, as well as many statues and inscriptions depicting a society that is humanist, harmonious and has a high spirit of mutual cooperation.Keywords: acculturation, architecture, plaosan temple